Neoliberalism and austerity in Spain, Portugal and South Africa: the revolution of older persons - Ornellas, A.; Martínez-Román, M.-A.; Tortosa-Martínez, J.; Casanova, J. L.; Guerreiro, M. D.; Engelbrecht, L. K. (Journal of Gerontological Social Work, 2017)
In Portugal, Spain and South Africa, there has been a noted anti-neoliberal resistance, marked by the significant participation of the older generation in protest movements. Changing demographics, the global financial crisis, unemployment, poverty, and the reliance of the family nucleus on the pensioner, coupled with neoliberal and austerity-based reductions to welfare programmes, pensions, health, and social care, has caused the “silver revolution”. As a population group that is often considered to be less politically active and robust members of society, such resistance is a noteworthy moment in society that needs to be considered and responded to.